FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU REMAJA JALANAN TERHADAP KESEHATAN REPRODUKSI DI YAYASAN PEMBINA ASUHAN BUNDA (YPAB) KOTA BATAM. - Rahmawati, Anggi; Susanti, Susanti (Universitas Batam, 2019)
The results of the 2012 Basic Indonesian Health Survey show that adolescent reproductive health shows that adolescents' knowledge of reproductive health is inadequate. It can be seen that only 35.3% of adolescent girls and 31.2% of male adolescents aged 15-19 know that women can get pregnant with one time sexual intercourse. The level of knowledge of male adolescents in the form of understanding the symptoms of sexually transmitted infections in men is 16.4% and in women is 6.1%, while the level of knowledge of adolescent girls is in the form of understanding the symptoms of sexually transmitted infections that occur in men, 15.8% and in women. 15.3% (Ministry of Health RI, 2015 in Ningsih 2016). The research objective was to know the factors related to the behavior of street adolescents on reproductive health. Analytical survey research method with cross sectional approach. Conducted in May-August at the Batam City Bunda Orphanage Development Foundation. The population is 101 respondents, the number of samples is 50 respondents, using a questionnaire. Data analyzed using Chi-square. The results of the study (56.0%) respondents lacked knowledge about reproductive health, (54.0%) respondents had negative attitudes about reproductive health behavior, (68.0%) respondents had poor peer influence on reproductive health behavior, (62.0 %) respondents have poor access to information media on reproductive health, (70.0%) respondents do not have reproductive health behavior. Conclusion There is a relationship (p-value = 0,000) between the knowledge of street adolescents about reproductive health and reproductive health behavior, there is a relationship (p-value = 0.002) between the attitudes of street adolescents about reproductive health, there is a relationship (p-value = 0,000) between friends peer street adolescents with Reproductive Health behavior. There is a relationship (p-value = 0,000) between access to information media and Reproductive Health behavior. Suggestions for the Mother's Care Development Foundation (YPAB) provide counseling to street youth about the impact of not having good reproductive health behavior.